PERBANDINGAN PELUMAS SEMI SINTETIK TERHADAP TEKANAN KOMPRESI, TEMPERATUR MESIN DAN EMISI GAS BUANG - Wahyudiansyah; M. Arsad Al Banjari (Program Studi Teknik Otomotif, Politeknik Hasnur, 2019)
Lubricants are chemicals that are generally in the form of a liquid given between two moving objects to reduce friction. This study aims to compare 3 types of semi-synthetic oil with different additives in each oil. The results show that the Compression Pressure shows Oil Samples 3 greater compression pressure than Oil Sample 1 and Oil Samples 2. Engine Temperature shows at 1500 rpm engine speed. The best temperature for the engine is the Oli sample 3 at a temperature of 48.5 ° C. At 3500 rpm engine speed The lowest engine temperature is Oil sample 3 is at a temperature of 65.5 ° C and engine speed is 5500 rpm Temperature Engine Oil sample 1 is at a temperature of 83.7 ° C, Oil sample 2 is at a temperature of 81.7 ° C and Oil Sample 3 are at 80.9 ° C. Exhaust Gas Emission at 1500 rpm engine speed The least amount of Carbon Monoxide (CO) is Oli 3 by 0.003%. At engine speed 3500 levels of Carbon Monoxide (CO) are the fewest, namely Oil sample 3 of 0.53%. At engine speed 5500 levels of Carbon Monoxide (CO) with a little Oil Sample 1 of 1.26%. At 1500 engine rotation the level of Hydrocarbon (HC) Oil Sample 2 is 186 ppm. At engine speed 3500 levels of Hydrocarbon (HC) Oil Sample 3 amounted to 81.6 ppm. At engine speed 5500 levels of Hydrocarbon (HC) Oil Sample 2 amounted to 122.3 ppm. At engine speed 1500 levels of Carbon Dioxide (CO2) at least 3 Oil Samples of 0.41%. At engine speed 3500 levels of Carbon Dioxide (CO2) are a little Oil Sample 3 of 0.5%. At engine speed 5500 levels of carbon dioxide (CO2) in the 1 sample oil exhaust emission of 2.1%. Oxygen levels (O2) in Exhaust Gas Emissions from all Oil Samples and engine speed variations do not change. the figures obtained are 20.90%. Keywords: Compression Pressure, Engine Temperature and Exhaust Emissions